(untitled) (Communications in Mathematical Research, 2021)
In this paper, by using the balancing method and the extended tanh-function method, we obtain the exact traveling wave solutions of Kundu equation with fifth-order nonlinear term. Applications of this method to some other nonlinear partial differential equations are also presented.